Surgical management of a rare case of mechanical intestinal ileus with extra-luminal adhesions between jejunal loops due to a linear foreign body in a Murrah buffalo - Singh, Bhanu Pratap; Mehra, Shivansh; K.M., Manjusha; Saxena, A.C.; Amarpal; K.S., Kamalesh Kumar; R., Prarthana (Indian Journal of Veterinary Surgery, 2026)
-